Impact of adding various nano materials in the efficiency of single slope solar still: A review. (2020) - Naveenkumar, R.; Gurumoorthy, G.; Kunjithapatham, Gautham; Anbu chellappan, R.; Bharath, A.; Ravichandran, M.
Abstract: The availability of potable water is exhausting nowadays due to tremendous reduction and pollution created by human being. Hence desalination using single slope solar still paves an economic and efficient way to generate clean drinking water from brackish water, in comparing to various contamination removing processes. Solar desalination method using still is uncommon, as it production rate and thermal performance is low. Various researchers have carried out different experimental modifications and inclusions of different nanomaterials in the base fluid of the solar still to enhance the distillate. This present review is done to evaluate and understand the influence of adding various nanomaterials in the solar still base fluid towards the production rate and heat transfer characteristics. This survey is adequate to enhance the knowledge level of the future researchers in this field and also assist numerous researchers in selecting the significant process and modification that elevate the production rate of the single slope (SS) solar still.